Role of Urinary Apolipoprotein A1 level in Predicting Development of Cancer of Urinary Bladder (Bangladesh Critical Care Journal, 2025)
Background: Urinary bladder cancer is the tenth most common malignant condition globally. Now incidence and prevalence of bladder cancer is gradually increasing. Urinary biomarker can play an important role for the diagnosis of urinary bladder cancer. Urinary apolipoprotein A-1 is a non–invasive biomarker. In this study, we evaluate the role of urinary apolipoprotein A-1 in predicting development of urinary bladder cancer. Methods: This cross-sectional comparative study was conducted in the Department of Laboratory Medicine, department of Urology, BMU. Total study subjects were 52 in number of which 26 were urinary bladder cancer patients (group I) and 26 were healthy subjects (group II). After taking informed written consent, 5 ml of urine was collected for estimation of urinary apolipoprotein A-1 in the Department of Laboratory Medicine by ELISA principle. After data collection and processing, all statistical analysis were done by SPSS version 22.0. Results: The mean urinary apolipoprotein A-1 level was found 47.95±41.90 ng/ml in group I and 6.21±7.01 ng/ml in group II. The difference was statistically significant (p< 0.05) between two groups as evidenced by the unpaired t-test. In ROC curve analysis a cut off value of 20.28 ng/ml for urinary apolipoprotein A-1 showed highest sensitivity (70.83%) and specificity (92.85%). The area under curve (AUC) of urinary apolipoprotein A-1 level was 0.899, indicating its effectiveness in predicting development of malignancy of urinary bladder. Conclusion: Urinary apolipoprotein A-1 level can be a promising biomarker in predicting development of urinary bladder.Bangladesh Crit Care J March 2025; 13 (1): 46-50